Antifatigue action of the 5-(furan-2-yl, 2-metylfuran-3-yl)-4-amino-1,2,4-triazole-3-thione alkyl derivatives - D. M. Danilchenko (Фармацевтичний журнал, 2018)
Body fatigue has many definitions but in general it can be described as a feeling of heaviness which occurs at the initiation or support physical or mental activities related to work at their normal abilities. Fatigue can be divided into physical and mental fatigue.